The role of foreign direct investment in Kedah Darul Aman - Abdul Karim, Noor Al-Huda; Hassan, Sallahuddin; Othman, Zalila; Ahmad Samidi, Munzarina (2000)
Activities of foreign direct investment (FDI) in Kedah state are particularly evident in the manufacturing sector, which is the most dynamic sector of Kedah's economy. For the purpose of this study, 53 foreign companies under administration of Kedah State Development Corporation (KSDC) were carefully selected